ARSITEKTUR ENTERPRISE SISTEM INFORMASI CENTRALIZED TRAFFIC CONTROL (CTC) KERETA API - Debora ERP (Jurnal Inkofar, 2017)
This research have a purpose to analyze and provide the design of CTC Information system in railway transportation (train), which use EAP (Enterprise Architecture Planning) method, in order to maximize the use of CTC which emphasize on digital business. In this case, Digital business, rail way in a small station is integrated to a system supporting CTC which could help the rail-driver in their job. The center of railway transport also could effectively control all of the transport and use of rail in the small stations.